PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Pada PT. AJ. Bringin Jiwa Sejahtera Kantor Semarang) - Mohamad Ciswo Utomo, 08.05.51.0134; Wanuri, Wanuri (Students Journal of Economic and Management, 2012)
The purpose of this research is to verify the effects of leadership, motivation, and work environment toward the performance of employees at âPT AJ Beringin Jiwa Sejahteraâ Semarang. The populations of this research are all employees of âPT AJ Beringin Jiwa Sejahteraâ Semarang. In this research, the researcher uses all populations that there at the company and the method called âcensus methodâ, because the amount of the populations are only 69 employees, and all of the populations are also the samples. The collected data are analyzed using the âfactor analysisâ to verify the validity of question items, âcronbach alpha formulaâto verify the instrument reliability, âregression analysisâ to verify the effect partially of each independent variables that are verifiedby the determination coefficient and fit model test to verify and prove the effect partially of each independent variables. The hypothesises are : (1) the result of statistic calculation with the linear regression analysis can be shown by the regression equation Y= 0,275 X1 + 0,380 X2 + 0,204 X3. From the regression equation, we know that leadership, motivation, and work environment havethe positive and significant effect towards the performance of employees. (2) The result of determination coefficient calculation is 0,439. It means that independent variables (leadership, motivation, and work environment) have the role as big as 43,9% simultaneously, can describe the dependent variable (performance). While the rest, 56,1% is described by the other variables that donât used in this research. (3) From the hypothesis that used in this research, we can conclude that : 1. There are positive and significant effects between leadership towards the performance of employees. 2. There are positive and significant effects between motivation towards the performance of employees. 3. There are positive and significant effects between work environment towards the performance of employees.Keywords : Leadership, Motivation, Work Environment, Performance of Empoyees